O cuidado ao recém-nascido na perspectiva da integralidade [manuscrito] :saberes e práticas no cotidiano da UTIN - Elysangela Dittz Duarte (2007)
This study had the objective of analyzing the elements that assure holistic care based on the practice of health workers in the intensive care unit of the Sofia Feldman Hospital. In order to attain the objectives, we chose a qualitative methodology, guided by theoretical-methodological dialectics. The study was carried in this hospital in Belo Horizonte, State of Minas Gerais, Brazil, and the subjects were ten health workers caring for newborn babies at the Intensive Care Unit and seven parents ofpatients. Data was collected through a structured workshop at four different moments: ice-breaking, individual reflection, group reflection, summary and evaluation. The workshop was held separately for the health workers and the parents. Participant observation was used based on situations of care for the neonates. For treating and analyzing the data collected, we chose discourse analysis, from which arose empirical categories: health acts that show holistic care; holistic care of health work: potentials, achievements and challenges; experience in the ICU teaches and challenges at each moment; possibilities in the life of theneonate: ways of being in life; the challenges of the team in their daily work to build holistic care. From the research data, it was possible to see the potential of the practice of health workers guided by holistic care, reaffirming the importance of team work and making it possible to learn acts of health that bring about holistic care or which do not show it. It can be seen that the presence of the mother changes the relations and environment in the neonatal ICU and imposes a constant rethinking andre-planning of the work of health professionals, demanding more from the health team. The challenges to be overcome by the team to build holistic care were understood, such as, improving communication between health workers, health workers and mothers, strategies which support the team, seeking to coordinate the work between different health workers and the different points of healthcare, using the presence of the family in the ICU and their unique position of observation to build holistic health practices and to build, together with the family and the healthcareservices, possibilities for these children to be able to go home, considering their ways of being in life.